Estudo do desempenho de um motogerador a partir da combustão de diferentes misturas de gasolina-etanol - Viola, Matheus [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Currently, not only in Brazil, but also all over the world, one of the most discussed topics in the energy field is related to the availability of energy resources and its use in existing machines. Based on this, there is a need to optimize the performance of current engines, considering the possible blends between fossil and renewable fuels. These different blends have influence on the operating parameters of an engine (power, voltage, current) as well as exhaust gases emitted (CO, CO2, NOx). Thus, in this undergraduate thesis, it is proposed to study the performance of a power generator and also to evaluate the emissions generated during the combustion of different gasoline-ethanol blends for different loads applied. The tests were performed on a power generator coupled to an internal combustion engine (Otto cycle). The experimental workbench was instrumented in order to measure the values of voltage, current, power and the emissions generated during the combustion. The statistical methodology called Response Surface Methodology (RSM) was applied with 3 replicates at the center point, 4 axial points and 22 combinations, totalizing 11 trials that were randomly performed, varying the percentage of ethanol and also the applied load. Based on the measurements, the response surfaces were obtained, and the statistical significance was determined by the analysis of variance (ANOVA). It was observed that the increase in the ethanol percentage in the blend had a small influence on the operating parameters of the power generator, but it was observed that the variations in the percentages of each one of the fuels had a big influence on the exhaust gases like CO2, NOx and O2

Atualmente, não só no Brasil, mas como no mundo todo, um dos temas mais discutidos é relacionado à disponibilidade de recursos energéticos e seu aproveitamento nas máquinas existentes. Com base nisso, surgiu-se a necessidade de otimizar o desempenho dos motores atuais, considerando as possíveis misturas de combustíveis fósseis e renováveis. Essas diferentes misturas podem influenciar os parâmetros de funcionamento de um motor e também os gases emitidos na exaustão (CO, CO2, NOx). Assim, neste trabalho de graduação propõe-se estudar o desempenho de um motogerador e avaliar as emissões geradas na combustão de diferentes misturas de gasolina-etanol para diferentes cargas aplicadas. Os testes foram realizados em um gerador de energia acoplado a um motor de combustão interna do ciclo Otto. A bancada experimental foi instrumentada de forma a medir os valores de tensão, corrente, potência e emissões geradas na combustão. A metodologia de planejamento estatístico denominada Response Surface Methodology (RSM) foi aplicada com 3 repetições no ponto central, 4 pontos axiais e mais 22 combinações, totalizando 11 ensaios que foram realizadas aleatoriamente variado-se a porcentagem de etanol na gasolina e a carga aplicada. A partir das medidas, foram obtidas as superfícies de resposta, sendo que a significância estatística foi determinada pela análise de variância (ANOVA). Os resultados mostraram que o aumento da porcentagem de etanol na mistura pouco influenciou os parâmetros de funcionamento do motogerador, mas observou-se que as variações nas porcentagens de cada um dos combustíveis tiveram uma grande influência nos gases de exaustão (CO2, NOx e O2)
Performance study of a motor generator from the combustion of different gasoline-ethanol mixtures
Keywords: Etanol; Gasolina; Planejamento experimental; Ethanol